(untitled) (Research, Society and Development, 2023)
Using composite resin in modern dentistry in Class II posterior restorations allows us to recover morphology and functionality in an affected tooth structure. Microleakage in the marginal sector of a tooth may be due to several factors, one of the main ones being the low polymerization shrinkage and stress to which the material is subjected. In addition, a good restoration prevents the infiltration of bacteria into the tooth. The objective was to determine the degree of marginal microleakage in Class II cavities restored with resin in the Latin American population employing a literature review. Materials and methods. In the present descriptive, cross-sectional, and retrospective study, articles referring to the subject in a maximum study time of 5 years were chosen, in addition to the search in literature sources such as PubMed, SciELO, Google Scholar, and Elsevier. Results. Microleakage is a post-operative complication found in most dental restorations with a 56% margin of failure from lack of polymerization shrinkage and other variables. Conclusion. Microleakage is a common problem during restoration; it is vital to know the product we use and its correct use. In addition, type II cavities are a challenge for any clinician during surgery.